+0  
 
0
260
1
avatar+397 

deleted.

 Jun 12, 2019
edited by sinclairdragon428  Nov 20, 2019
 #1
avatar+111438 
+1

\(4 - \frac{3x + 1}{4} = x + \frac{3x + 14}{2}\)      get common denominators

 

16 -[3x + 1]             2x + 3x + 14

__________   =       ___________         

       4                          2

 

15 - 3x            5x  + 14

______    =   __________          cross-multiply

     4                       2

 

2 ( 15 - 3x)  =  4(5x + 14)     sinmplify

 

30 - 6x  =  20x  + 56         add 6x to both sides, subtract 56 from both sides

 

-26  =  26x       divide both sides by  26

 

-1 = x

 

cool cool cool

 Jun 12, 2019

14 Online Users

avatar
avatar
avatar